Characterization of rectum-colon cancer in Cienfuegos province from 1995 to 2000. - Itengré Ouédraogo; Julio Pablo Miñoso Andina; Juan E. Domínguez Suárez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2003)
Background: In spite of the recent advances in the medicine field which permit a better diagnosis and to establish treatments in early stages of the diseases, the colon and rectum cancer have shown an ascendant curve line in terms of incidence and mortality worldwide. There is an incidence around 11 000 new cases per year in Cuba, and it constituted the third cause of death in Cienfuegos province from 1988 to 1997. Objectives: To characterize the colon and rectum cancer in Cienfuegos province from 1995 to 2000. Methods: a descriptive, retrospective study carried out at the University Hospital ¨Dr. Gustavo Aldereguía Lima¨ in Cienfuegos city, Cuba in order to characterize these kinds of cancer from 1995 to 2000. 221 patients were under studied after being surgically treated in the General and Colon Proctology Service with a diagnosis of colon and rectum neoplasia during those years. Data were obtained from the clinical records and biopsy reports. This work is just the first parte of the investigation, that's the reason complications and mortality are not mentioned at all. Results: there is a higher frequency of occurrence in the female patients and in patients older than 60 years although a 5 % of the cases were 40 years old or younger. The most frequent site was the rectum and hemorrhage was the most predominant clinical manifestation. The adenocarcinoma was presented in 90.5% and the highest per cent of the cases were diagnosed in B and C Duke's stage. Surgery was applied with curative intention in the majority of the patients meanwhile palliative surgery was predominant in the cases with occlusive clinical form. There were patients in C Duke´s stage that did not received chemotherapy treatment.